Impacto dos serviços de farmacia clínica em unidades de terapia intensiva: uma revisão sistematica - Santos, Adriano da Silva (2016)
Introduction: The complexity of the processes and the medical conditions of patients increase the probability of errors and makes patient safety a critical process in intensive care units (ICU). Although knowledge about the activities carried out by pharmacists in intensive care has increased in recent years, there is a lack of systematic reviews on the topic. Thus, the aim of this study is to show the impact of clinical pharmacy services in adult ICUs. Methods / Study Design: A systematic review was conducted, recorded in PROSPERO with nº CRD42015019592. Quasi-experimental intervention studies, cohort, case-control and clinical trials were included. The selection of studies was conducted in COCHRANE, Scient Direct, LILACS, PubMed, Scopus and Web of Science databases, published from January 2000 to May 2015. Results and Discussion: We identified 1589 studies, which after the selection process resulted in 24 studies included in the review. The main services developed were identification of adverse drug events and drug-related problem (9), educational activities (4), management of therapies/specific patients (3) management of patients on mechanical ventilation (3) development and implementation of assistance protocol (4) and interventions to reduce drug consumption and costs in the ICU (1) It was observed a reduction in the prescription errors (190.5 vs 62.5 per 1000 patients/day), the percentage of appropriate use of stress ulcer prophylaxis (14.4 vs. 6.0, p <0.001), better control glucose (211 vs 168 mg / dL, p = 0.03), reduction of days on mechanical ventilation (338.4 vs. 178.1, p = 0.004), the better dose adjustment for patients on renal replacement therapy, reduced costs and better drugs management practices. Conclusions: The clinical pharmacy services have a positive impact on clinical and economic outcomes's adult ICU patients. However, there was no impact of these services on the length of stay in ICU, length of hospital stay and mortality rates.